Coffee producers’ perspectives of blockchain technology in the context of sustainable global value chains - Singh, Christina; Wojewska, Aleksandra N.; Persson, U. Martin; Bager, Simon L. (Frontiers in Blockchain, 2022)
Transparency and equitability are key for improved sustainability outcomes in global value chains. Blockchain technology has been touted as a tool for achieving these ends. However, due to the limited empirical evidence, claims on transparency and sustainability benefits are largely theoretical. We lack an understanding of the benefits and drawbacks for upstream actors within global value chains and how this affects technology adoption. Addressing this gap, we conduct an empirical study to identify the drivers and obstacles for coffee producers in Colombia in adopting blockchain. We base our research on an event-driven and permissioned blockchain model, specifically designed for this research. Applying the Participation Capacity Framework and conducting semi-structured interviews with coffee producers and key informants, we analyze adoption attitudes towards the blockchain application. We further identify opportunities and drawbacks from the producers’ perspective. We set these findings in the context of the Global Value Chain research, considering the existing power relations in the coffee value chain. The top-down nature of blockchain projects raises distributive concerns, as resource investments, implementation burden, and risks are significantly higher upstream, whereas downstream lead firms will benefit most. We identify data squeeze as an additional channel of sustainable supplier squeeze relevant in the case of blockchain initiatives. Data squeeze implies lead firms turning the data obtained through, likely unpaid, labour of blockchain participants into a monetizable assets and marketable value through branding and advertisement. Based on the findings, we identify potential design dimensions and implementation features that can contribute to materializing producer benefits, thus mitigating the risk of a sustainability-driven supplier squeeze.